ESTIMATION OF THE SOCIAL AND PSYCHOLOGICAL ADAPTATION STATE OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS OF CHERNIVTSI IN THE CONDITIONS OF WAR. - Shuper, S. (My University, 2023)
The article is devoted to establish and evaluate the state of social and psychological adaptation of students of middle courses of higher educational institutions of Bukovyna depending on the influence of medical factors and individual characteristics of individuals in the conditions of war in Ukraine. The revealed results differed significantly from the pre-war indicators and demonstrated a decrease in the level of social aThe article is devoted to establish and evaluate the state of social and psychological adaptation of students of middle courses of higher educational institutions of Bukovyna depending on the influence of medical factors and individual characteristics of individuals in the conditions of war in Ukraine. The revealed results differed significantly from the pre-war indicators and demonstrated a decrease in the level of social and psychological adaptation in general in all studied students. The presence of a negative impact of a decrease in socio-psychological adaptation on motivation to study and on current study results is also noted. This situation can complicate the professional formation of specialists of this profile and cause difficulties in self-regulation in the future, which requires the development of systematic measures to correct influencing factors of medical and non-medical origin in order to improve their social and psychological adaptationnd psychological adaptation in general in all studied students. The presence of a negative impact of a decrease in socio-psychological adaptation on motivation to study and on current study results is also noted. This situation can complicate the professional formation of specialists of this profile and cause difficulties in self-regulation in the future, which requires the development of systematic measures to correct influencing factors of medical and non-medical origin in order to improve their social and psychological adaptation